Speaking populism: ideational vs. issue-based theories of populism - Busby, Ethan C.; Carlin, Ryan E.; Hawkins, Kirk A.; Littvay, Levente (Frontiers in Political Science, 2025)
Debates on the nature and causes of populism persist in the public and among academics. We test two contemporary theories of populism – issue-based and ideational – by exploring their implications for the expression of populist rhetoric among citizens. In a large scale, cross-national experiment (N 18,000), we prompt the expression of populism through an elaboration task exploring the causes and solutions to current policy problems. The task frames the discussion as the product of either responsible actors (populist framing) or impersonal circumstances (non-populist framing). Three findings emerge: (1) different political issues provoke more populism than others; (2) framing policy problems in terms of responsible actors increases the expression of populism across countries and participants; and (3) political issues combine with respondents’ ideology to prompt populism in predictable ways. These findings support the arguments of the ideational approach.